Design and fabrication of drainwater energy converter - Mukrim, Mufrid Sufyan (2024)
This study focuses on designing a mini hydroelectric system for harnessing the energy of rainwater flowing through drainpipes in Southeast Asia, where frequent rains are common. The problem addressed is the significant waste of potential energy in residential, commercial, and urban water drainage. The project's main objectives are to design and fabricate a drain pipe energy converter using SolidWorks 2021. Methodologies include technical drawing in SolidWorks and fabrication using available machinery at UITM Pasir Gudang, with materials chosen based on market availability. The expected outcome is a portable, efficient system that generates electricity from drain water, promoting energy sustainability.